Tridentate acylhydrazone copper(II) complexes with heterocyclic bases as coligands. Synthesis, spectroscopic studies, crystal structure and cytotoxicity assays. (1st February 2022) - Burgos-López, Yacelis; Balsa, Lucia M.; Piro, Oscar E.; León, Ignacio E.; García-Tojal, Javier; Echeverría, Gustavo A.; González-Baró, Ana C.; Parajón-Costa, Beatriz S.
Graphical abstract: Two new copper(II)-hydrazone complexes with 2, 2́ bipyridine or 1, 10 phenanthroline as coligands were synthesized and characterized by spectroscopic methods. Their molecular structures were confirmed by single crystal X-ray diffraction. Both complexes were evaluated as antitumour agents. They showed higher cytotoxic activity against lung, bone and breast cancer cells lines than cisplatin. Highlights: Two ternary Cu(II) hydrazone complexes were synthesized and characterized. The complexes crystallize in a CuO2 N3 distorted square pyramidal environment. The hydrazone adopts different tautomeric forms in the environment of each compound. EPR data are consistent with the dx 2 -y 2 ground state determined by XRD. They are more cytotoxic than cisplatin on lung, bone and breast cancer cells lines. Abstract: Two new penta-coordinated copper(II) hydrazone coordination compounds with 2, 2́ bipyridine (I) or 1, 10 phenanthroline (II) as coligands are synthesized and characterized in the solid state and in solution by spectroscopic methods (FTIR, Raman, UV–vis, EPR). Single crystal X-ray studies show that they have closely related molecular structures with the copper center in a distorted square pyramidal O2 N3 environment. The N -acylhydrazone, 4-hydroxy-NŃ-(E)2-hydroxy-3-methoxybenzylidene]benzohydrazide, H2 L, coordinates tridentate through its ONO donor atoms as monoanion (HL - ) in the cationic complex (I), [Cu(HL)(bipy)](NO3 ). During the period that takes the synthesis reaction of compound (II), [Cu(L)( o -phen)] to complete, keto-amine to enol-imine tautomerization of H2 L occurs and the hydrazone coordinates tridentate as dianionic ligand (L 2- ). The fivefold coordination sphere of the complexes is completed with the nitrogen atoms of the respective coligands. Cytotoxicity studies against bone (MG-63, IC50 (I)  = 5.6 ± 1.0, IC50 (II)  = 3.5 ± 0.3), breast (MCF7, IC50 (I)  = 10.8 ± 1.9, IC50 (II)  = 4.0 ± 1.3), (MDA-MB-231, IC50 (I)  = 11.4 ± 0.6, IC50 (II)  = 5.3 ± 0.2) and lung cancer cells (A549, IC50 (I)  = 7.7 ± 0.7, IC50 (II)  = 7.0 ± 0.4) reveals increased effectiveness of both complexes compared with the free ligand, the copper nitrate salt and the reference metallodrug cisplatin (CDDP).